Molecular detection of Lotmaria passim in honeybees in Japan. (April 2023) - Yamamoto, Satomi; Nakamura, Sakure; Nakayama, Kazuhiko; Kusakisako, Kodai; Watanabe, Koh; Ikadai, Hiromi; Tanabe, Taishi
Abstract: Crithidia mellificae (C. mellificae) and Lotmaria passim (L. passim) are trypanosomatids that infect Apis mellifera. We analyzed the prevalence of C. mellificae and L. passim in six regions of Japan from 2018 to 2019. The detection rate of C. mellificae was 0.0% in all regions, whereas L. passim was detected in 16.7%–66.7% of the honeybees. L. passim was detected at a significantly lower rate in the Cyugoku-Shikoku region than in other regions. Furthermore, phylogenetic analysis of the internal transcribed spacer 1 (ITS1) locus of related species was performed. All the samples in this study could be assigned to the L. passim clade. This study reveals that L. passim infection is predominantly prevalent in Japan. Further epidemiological surveys are needed to clarify the prevalence of C. mellificae infection in honeybees in Japan. Graphical abstract: Unlabelled Image Highlights: L. passim infection was predominantly prevalent in Japan. L. passim was significantly less prevalent in Chugoku-Shikoku region. C. mellificae was not detected.